Genome-Wide Analysis of Soybean Polyamine Oxidase Genes Reveals Their Roles in Flower Development and Response to Abiotic Stress - Yang Yu; Bohuai Jin; Meina Gao; Ke Zhang; Zhouli Liu; Xiangbo Duan (Plants)
Polyamine oxidase (PAO) is an important enzyme that functions in the catabolism of polyamines. While plant PAOs have been studied in several species, there is a lack of research on this gene family in soybean (Glycine max L.), one of the major food crops worldwide. Here, a genome-wide analysis identified 16 GmPAOs from the soybean genome, which were unevenly distributed in nine soybean chromosomes and were then phylogenetically classified into three groups. Collinearity analysis identified 17 duplicated gene pairs from the GmPAO family, and their Ka/Ks values were all less than one, indicating that the GmPAO family has undergone purifying selection during evolution. Analyses of the conserved motif and gene structure revealed the sequence differences among the GmPAOs of the three groups, suggestive of their functional differentiation. Additionally, the prediction of the secondary and tertiary structure of the GmPAOs provided a further basis for revealing their biological functions. A number of cis-acting elements relevant to development, phytohormone, and stress response were discovered in the promoter regions of the GmPAOs, which might be responsible for their functional diversities. Expression pattern analysis indicated that more than half of the GmPAOs showed preference in flower, two showed specificity in stem and shoot apical meristem, whereas four were barely expressed in all samples. Expression profiling of the GmPAOs also revealed that they were involved in the response to abiotic stresses, including cold, drought, and especially submergence stress. All these results lay an important foundation for further characterizing the functional roles of GmPAOs in soybean development and response to abiotic stresses.